1990
DOI: 10.1016/0304-3959(90)90062-i
|View full text |Cite
|
Sign up to set email alerts
|

Self-administration of morphine in bone marrow transplant patients reduces drug requirement

Abstract: Bone marrow transplant recipients were randomly assigned to receive morphine by either continuous infusion (32 patients) or self-administration of small boluses (patient-controlled analgesia (PCA), 26 patients) for control of chemoradiotherapy-induced oral mucositis pain. All patients received morphine for a minimum of 9 days and most required morphine for at least 14 days. Patients rated their pain and side-effect intensity daily using visual analogue scales. Patient pain ratings did not differ between the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 18 publications
2
17
0
1
Order By: Relevance
“…All seven studies found PCA to be an effective mode of opioid administration in the management of mucositis pain. Studies comparing PCA to a continuous infusion reported that total opioid use was lower in patients receiving PCA [43,56,67]. One study examined the use of a PCA system where patients adjusted the rate of a continuous morphine infusion to increase or decrease their plasma morphine concentration.…”
Section: Patient-controlled Analgesiamentioning
confidence: 99%
“…All seven studies found PCA to be an effective mode of opioid administration in the management of mucositis pain. Studies comparing PCA to a continuous infusion reported that total opioid use was lower in patients receiving PCA [43,56,67]. One study examined the use of a PCA system where patients adjusted the rate of a continuous morphine infusion to increase or decrease their plasma morphine concentration.…”
Section: Patient-controlled Analgesiamentioning
confidence: 99%
“…Specifically, many surveys have demonstrated that opioid doses typically stabilize during long term administration (17,24,62,(64)(65)(66)69,99,(109)(110)(111)(112)(113). When the need for dose escalation occurs, it is usually readily explained by a worsening physical lesion (24,114) or a changing psychological state (115).…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…The opioid can be delivered either by a continuous infusion (CI), by a PCA device or by PCA combined with CI in selected circumstances, such as in patients with mucositis. 57,58 Patient-controlled analgesia relies on a pump that is programmed to deliver boluses at a lockout time (for example 15 min) until significant pain relief occurs. The administration of a loading dose of the opioid is recommended before initiating PCA to achieve rapid analgesia and predict subsequent PCA needs (Table 2).…”
mentioning
confidence: 99%